Detection, genotyping & transcriptome analysis of s.typhi & s paratyphi form well water & its association with geographical clustering on enteric fever - Ismail, Aziah (Pusat Pengajian Kesihatan, 2015)
A total number of 936 waters samples were collected from the typhoid locality in the year 2011-2013. S. Typhi was isolated from 2 samples whereby one them are from the outbreak cases in Pasir Mas, Kelantan dan the other one is the sporadic cases. Multiplex PCR showed S. Typhi positives in 19 cases suggesting that the PCR is more sensitive than the culture method. GIS analysis showed model of relationship between water positivity and cases. The S. Typhi isolated from water samples from outbreak area was genotyped together with the S. Typhi isolated from stools of food handlers in the same outbreak area. The pulse-field gel electrophoresis (PFGE) showed similar pattern with the isolates from well water. The findings suggested that the carriers among food handlers had contaminated the water and causing the outbreak. A representative S Typhi isolated from stools of food handlers and one of the S. Typhi isolated from water samples were undergone genome and RNA sequencing. The results showed that there are several genes that can differentiate between the two isolates. Transciptome analysis showed that 1272 genes were upregulated when S. Typhi was incubated in well water compared to the our genome analysis whereas 1065 genes were upregulated compared to CT18 genome (reference genome sequence in GenBank, NCBI). Further downstream analysis will be continued using other future grants.